Comunidades indígenas de la provincia de Chimborazo, Ecuador: permanencia de la sombra del régimen de hacienda - Tuaza Castro, Luis Alberto (2014)
This paper analyzes current indigenous politics, from an approachto the indigenous communities historical process in the area of Guamote Totorillas, Ecuador. It is argued that after the dissolution of the hacienda system new forms of indigenous leadership emerged. The pervasiveness of ancient forms of leadership stemming from the hacienda system, though, prevent communities efforts to achieve unity and the design of a long term political project.